The Influence Of Work Experience, Motivation, And Organization Commitment On Employees Career Development, PT. Indocater - Lucky Keta Ritanti; Luis Marnisah (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this research specifically is to get the results of an analysis of work experience, motivation, and organizational commitment to employee career development at PT. Indocater, either partially or simultaneously. The research method uses descriptive and verification surveys; field data collection uses questionnaires, interviews, and documentation techniques. This research is associative, in which there are variables that are related and can influence other variables. The population of this research is 68 employees at PT. Indocater, taken as a sample of 68 employees. Data processing using SPSS analysis tools 25. Testing data using the t test, it was found that work experience affects career development with a t count of 5.056 > t table 1.668; there is an influence of motivation on career development with a t count of 2.623 > t table 1.668; there is an influence of organizational commitment on career development with a t count of 5.343 > t table 1.668; and work experience, motivation, and organizational commitment influence career development with a t count of 19.880 > t table 2.507; The common thread of research is that work experience, motivation, and organizational commitment have a positive and significant effect on employee career development. At PT. Indocater, both partially and simultaneously, strategies to enhance employee career development can be implemented by providing optimal training and motivation prior to work placement.